The value of Interferon β in multiple sclerosis and novel opportunities for its anti-viral activity: a narrative literature review - Bellucci, Gianmarco; Albanese, Angela; Rizzi, Caterina; Rinaldi, Virginia; Salvetti, Marco; Ristori, Giovanni (Frontiers in Immunology, 2023)
Interferon-beta (IFN-β) for Multiple Sclerosis (MS) is turning 30. The COVID-19 pandemic rejuvenated the interest in interferon biology in health and disease, opening translational opportunities beyond neuroinflammation. The antiviral properties of this molecule are in accord with the hypothesis of a viral etiology of MS, for which a credible culprit has been identified in the Epstein-Barr Virus. Likely, IFNs are crucial in the acute phase of SARS-CoV-2 infection, as demonstrated by inherited and acquired impairments of the interferon response that predispose to a severe COVID-19 course. Accordingly, IFN-β exerted protection against SARS-CoV-2 in people with MS (pwMS). In this viewpoint, we summarize the evidence on IFN-β mechanisms of action in MS with a focus on its antiviral properties, especially against EBV. We synopsize the role of IFNs in COVID-19 and the opportunities and challenges of IFN-β usage for this condition. Finally, we leverage the lessons learned in the pandemic to suggest a role of IFN-β in long-COVID-19 and in special MS subpopulations.